PARIWISATA KERAKYATAN (COMMUNITY BASED TOURISM) DAN PENGARUHNYA PADA KESEJAHTERAAN PETANI DI DESA BUDAYA KERTALANGU KOTA DENPASAR - L,PT. Kirana Pratiwi; N Sutjipta; IG. Setiawan AP (Universitas Udayana, 2017)
ABSTRACTCommunity Based Tourism and Its Impacts to the Welfare of Farmers in KertalanguCulture Village, Denpasar CityThe development of tourism in Bali until now has oriented in the mass tourismconcept that was dominated by investors through the development of large scale facilities toboost the local revenue. In the short term, tourism gives significant benefits to economic, butin the long run it will become a boomerang for economy. An alternative to the tourismproblem is the establishment of community based tourism which farmers as the subjectdirectly involve in tourism. The purpose of this research is to analyze the influence oftourism, empowerment, and participation on increasing the welfare of farmers. The study hadtaken in Subak Padanggalak, Kertalangu Culture Village. The sample has done withpurposive sampling which consist of 57 farmers. Technique analysis data using Partial LeastSquare (PLS) with Smart PLS program.The research results show that tourism potential has significant impact on farmersempowerment, and it has followed by farmers empowerment also have significant impact onthe farmer participation. In contrast, farmer’s participation have not significant onincreasing their welfare. This indicate that the farmer’s participation have not give opimalbenefit in supporting welfare of their life. Farmer have not look as the tourism subject. Therole of farmers and subak have limited to support the tourism development, which thefarmers have not involvement directly. It suggested the need that will be supported by privatesector to develop agriculture to agrotourism. Trough the development of agrotourism a lot ofagriculture commodities can be developed, and has been undertaken by variousmanufacturing agriculture products. The government through relevant agencies is expectedto provide capital access and market acces as well as various guidance in managingagricultural products as a tourism product, thus farmer having high competitiveness on skillenhancement and improving their well-being.Keywords: Community Based Tourism, Tourism Potential, Empowerment, Participation, theWelfare of Farmers.